Faktor-Faktor yang Mempengaruhi Kepatuhan Wajib Pajak dalam Penerimaan Pajak Penghasilan pada Kantor Pelayanan Pajak Pratama Malang Utara - Hasbi Maftuh Ardiansyah; Afifudin Afifudin; Siti Aminah Anwar (e_Jurnal Ilmiah Riset Akuntansi, 2023)
An increase in state revenue from the taxation sector as a source of financing that is still possible, based on the number of tax payments from year to year, is expected to increase in view of the increasing population. One type of tax that is a source of revenue is income tax. Income tax is a type of subjective tax that is obligated to be attached to the tax subject concerned. Taxpayer Awareness, Tax Sanctions, Tax Knowledge, and tax authorities play a very important role in the success of a taxation. The population in this study are individual taxpayers who are registered at KPP Pratama Malang Utara. Sampling in this study using the slovin formula. 99 data were used and processed using SPSS 29.0 for windows. The results of this study indicate that taxpayer awareness has an effect on income tax receipts, tax sanctions have an effect on income tax receipts, tax knowledge on income tax receipts, and tax authorities have no effect on income tax receipts.Keywords: Income tax, tax sanctions, tax knowledge, tax understanding, and tax authorities